Mengubah Keterbatasan Pelatihan Canva Untuk Anak Didik Pemasyarakatan (ANDIKPAS) Dalam Bisnis Dan Kemandirian Ekonomi - Guntoro Barovih; Fahmi Ajismanto; Febrianty (LOSARI DIGITAL, 2024)
Digital technology advancement is becoming increasingly important for business and education development. This article discusses the role of information technology for children in community service organizations, with an emphasis on LPKA. Canva's design classes are used to train designers and help them become more adept at enhancing their work and realizing their own business potential. The implementation method involves silent practice and demonstration, along with evaluation to ensure effectiveness. The evaluation results indicate a high level of enthusiasm and understanding from the participants as well as support from the LPKA. This training aims not only to increase students' keterampilan but also to prepare them for life after graduation, with the goal of eradicating negative stereotypes about former students and turning them into positive members of society